Prediction of Gestational Age in Osmanabadi Goats by Ultrasonic Measurement of Crown-Rump Length - Pati, Prasanna; Sahatpure, S.K.; Patil, A.D.; Kumar, Umesh; Jena, Basanti; Nahak, A.K.; Sharma , Laxman Prasad (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The objective of this study was to predict gestational age of Osmanabadi goats by real time ultrasonography using measurements of Crown Rump Length (CRL). CRL was measured  in 15 Osmanabadi goats, by transabdominal ultrasonography carried out on days 35, 42,  49, 56, 63 and 70 of gestation, those became pregnant after oestrus detection and natural  mating following oestrus synchronization in 30 does using double PGF2a injections 11 days apart.  Gestational age was calculated by using gestational equations derived from the linear regression  analysis. Results clearly demonstrated that biometric parameter CRL was significantly (P< 0.01)  correlated with gestational age (r= 0.988) and was a reliable index to predict gestational age  in Osmanabadi goats.
Keywords: Crown-Rump Length (CRL); Ultrasonography; Osmanabadi goats